Karakteristik Mutu Kimia Pempek dan Potensi Cemaran Logam Berat (Pb dan Cd) di Kota Palembang - Oby Dwijaya; Susi Lestari; Siti Hanggita (Universitas Sriwijaya, 2015)
The purpose of his research was to determine the chemical characteristics and the heavy metal (Pb and Cd) content on producers in Palembang. The research was conducted on February 2014 until March 2014. The results obtained in this study were analyzed using descriptive methods. Parameters observed were chemical analysis (moisture content, protein content, fat content, ash content and carbohydrate content) and analysis of heavy metals lead (Pb) and cadmium (Cd). Chemical characteristics of pempek lenjer in this study with the range of water content between 48.89%-66.92%, ash content 1.01%-5.80%, protein content 0.042%-2.027%, fat content 1.01%-1.67% and carbohydrates 22.64%-39.05%. Where as lead (Pb) < 0.0104 mg/kg was detected on concentration less than and cadmium (Cd) < 0.0006 mg/kg.